2008
DOI: 10.1667/rr1098.1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to 900 MHz Radiofrequency Radiation Induces Caspase 3 Activation in Proliferating Human Lymphocytes

Abstract: In this study, the induction of apoptosis after exposure to 900 MHz radiofrequency radiation (GSM signal) was investigated by assessing caspase 3 activation in exponentially growing Jurkat cells and in quiescent and proliferating human peripheral blood lymphocytes (PBLs). The exposure was carried out at an average specific absorption rate of 1.35 W/kg in a dual wire patch cell exposure system where the temperature of cell cultures was accurately controlled. After 1 h exposure to the radiofrequency field, a sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 52 publications
1
14
0
1
Order By: Relevance
“…PS exposure to the outer leaflet of the plasma membrane has previously been observed in human spermatozoa (40)(41)(42)(43). Consistent with results from previous studies showing a lack of PS externalization in various cell types after in vitro exposure to RF EMFs (16,44,45), no evidence of a change in PS externalization was found after a 1-h exposure of human spermatozoa to 900 MHz GSM radiation. The percentage of PS-externalizing living cells (Annexin V z PI 2 ) observed in the present study is in close agreement with the observations of Ricci et al (46) but differs from those of other studies (47,48).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…PS exposure to the outer leaflet of the plasma membrane has previously been observed in human spermatozoa (40)(41)(42)(43). Consistent with results from previous studies showing a lack of PS externalization in various cell types after in vitro exposure to RF EMFs (16,44,45), no evidence of a change in PS externalization was found after a 1-h exposure of human spermatozoa to 900 MHz GSM radiation. The percentage of PS-externalizing living cells (Annexin V z PI 2 ) observed in the present study is in close agreement with the observations of Ricci et al (46) but differs from those of other studies (47,48).…”
Section: Discussionsupporting
confidence: 91%
“…This may suggest an independence of the mechanisms of PS translocation and caspase activation in the physiology of spermatozoa. In some studies an increase in caspase activity after RF EMF exposure was observed that did not correlate with expression of markers of apoptosis (16,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There might be other ones, such as the reactive oxygen species or other non-thermal effects of microwave. Several studies demonstrated that microwave could cause cells apoptosis and the temperature was under 41°C [19][20][21]. The mechanism of muscle cell apoptosis in this study was complicated, and not exactly the same as that of tumor cell apoptosis in hyperthermia condition [22].…”
Section: Discussionmentioning
confidence: 71%
“…There are studies reporting controversial results on the activation of caspases and apoptotic responses due to continuouswave or modulated RF radiation exposure in different cell types. Palumbo et al (2008) reported increased caspase-3 activation in proliferating human lympochytes that were exposed to a 900 MHz RFR. On the contrary, Merola et al (2006) and Joubert et al (2006) found no significant effects on caspase-3 activity in human LAN-5 neuroblastoma and SH-SY5Y neuroblastoma cells after RFR exposure.…”
Section: Caspase-9mentioning
confidence: 99%